Blacks As Supervisors: A Study of Training, Job Performance, and Employers’ Expectations - Beatty, Richard W. (Academy of Management Journal, 1973)
This study of a training program designed for the development of black supervisors investigated the relationship of several training and nontraining variables with employers? evaluations of black supervisors? job performance. The results indicated that employers tended to evaluate performance not on factors related to program content or on task-related behaviors, but on other behaviors black supervisors demonstrated while at work.